Dampak Covid-19 Terhadap Standar Minimum Penilaian Pembelajaran di Kurikulum (K-13) - Windarto, Windarto (LoroNG: Media Pengkajian Sosial Budaya, 2020)
The Covid-19 pandemic has changed the stability of countries in the world, including in Indonesia, where various sectors of life are exposed, starting from the economy, social, health, and education. Education with the essential Kurikulum 2013 (K-13) had to be carried out through an online learning system from their respective homes with the help of technological devices. The two policies of the Minister of Education and Culture in the form of Circular Letter Number 4 of 2020 regarding the implementation of education during the Covid-19 period and the Decree of the Minister of Education and Culture Number 719/P/2020 concerning Guidelines for Curriculum Implementation in Education Units in Special Conditions serve as educational guidelines in which there is relaxation and flexibility in it. This study focuses on collecting and building data regarding the minimum standards of learning assessment in the essential Kurikulum 2013 (K-13). This research method is descriptive qualitative with a library research approach. Data collection system by accommodating, reading, recording, and processing various reading literature. The results show that the minimum standard of learning assessment is derived from the essence of the policies of the Minister of Education and Culture such as teachers are not burdened with completing the K-13 curriculum achievements in normal times, the substance of learning gives meaning and life skills to students, learning assessment is not in the form of numbers but rather a qualitative description of achievement of competence in students. Thus, an effective assessment technique is portfolio assessment and self-assessment which is dominant in the affective domain rather than psychomotor and cognitive. Pandemi Covid-19 telah merubah stabilitas negara-negara di dunia, termasuk di Indonesia yang mana berbagai sektor kehidupan terpapar mulai dari ekonomi, sosial, kesehatan, dan pendidikan. Pendidikan dengan kurikulum 2013 (K-13) esensial terpaksa harus dilakukan melalui sistem pembelajaran daring dari rumah masing-masing dengan bantuan perangkat teknologi. Dua kebijakan Mendikbud berupa Surat Edaran Nomor 4 Tahun 2020 tentang pelaksanaan pendidikan di masa Covid-19 dan keputusan Mendikbud Nomor 719/P/2020 tentang Pedoman Pelaksanaan Kurikulum Pada Satuan Pendidikan Dalam Kondisi khusus menjadi pedoman pendidikan yang mana terdapat relaksasi dan fleksibilitas di dalamnya. Penelitian ini berfokus pada pengumpulan dan bangunan data mengenai standar minimum Penilaian Pembelajaran Di Kurikulum 2013 (K-13) esensial. Metode penelitian ini adalah kualitatif deskriptif dengan pendekatan library research. Sistem pengumpulan data dengan cara mengakomodasi, membaca, mencatat serta mengolah berbagai literatur bacaan. Hasil penelitian menunjukkan bahwa standar minimum penilaian pembelajaran diturunkan dari esensi kebijakan-kebijakan Mendikbud seperti guru tidak dibebani untuk menuntaskan capaian kurikulum K-13 di masa normal, substansi pembelajaran memberi makna dan kecakapan hidup pada siswa, penilaian pembelajaran tidak berupa kuantitas angka melainkan deskripsi kualitatif tentang ketercapaian kompetensi dalam diri siswa. Dengan demikian teknik penilaian yang efektif dilakukan adalah penilaian portofolio, dan penilaian diri yang mana dominan ke ranah afektif dari pada psikomotorik dan kognitif.